Interests as the basis of corporate governance - shareholders’ profit versus social responsibility - Dubajić, Dunja (Pravni zapisi, 2018)
In the article, the author pointed out that determining the content of company’s interest is dialectically related to question of whether there is a particular company interest or it is just a set of different interests that are affected by the externalization of operating costs. Shareholders are usually designated as the owners of the company, so the protection of their interests is perceived as a priority. However, the company’s limited liability and the separation of ownership from management provide an exceptional capacity for independent action and therefor require protection of company’s separate interests. Classical theories about company relations limit the circle of participants to ones that are involved only in relations with a contractual nature. However, within the framework concept of corporate social responsibility (CSR), it is evident that there is essential importance of protecting company’s distinguished interests, and also the public interests personalized in interests of consumers, interests of the state and society. The stakeholder theory emphasizes fundamental significance of harmony in relations between stakeholders, so the value could be created in the long run, and that it is counterproductive to focus only on economic principles of value creation. It is impossible to ignore that the company itself is an entity with its own expectations, and if the interests of other stakeholders are removed, the only relevant company’s goal would be its existence, or the sustainability of its business. When the company’s interests are understood in this way, it is obvious that a long-term business policy forms the basic protection of those interests. CSR in modern sense is linked with the goal of sustainability, with a profitable nature as the most important factor of long-term business policy and sustainable development. However, as the contractual mechanisms are not enough to protect the stakeholders’ interests to a degree greater than company’s legal obligations towards its employees, consumers and creditors, there is a need for strong influence of imperative regulations in the field of CSR.